The technological revolution and its impact on current education: educational response to COVID-19 - Manzaba, Freddy Daniel Magallanes; Rodríguez, Marcos Alejandro Yánez (International research journal of management, IT and social sciences, 2021)
The Technological Revolution is one of the most important processes that emerged in the current era, better known as the “knowledge society '', which implies the introduction of Information and Communication Technologies (ICT) in the various contexts of society, such as in education. The subject of this document arises from the problems experienced around the world and the ignorance of the impact that the pandemic has caused in different aspects of current life. And it is that, because of one of the most serious diseases, countless strategies have been used that allow human beings to mediate their activities as they did previously. Education is one of the contexts that have been affected by this virus, in addition to being considered essential for the development of society, a National Educational Plan has been chosen within Ecuador, giving an immediate and favorable response to the process of teaching-learning, having technology as the main means of interaction. The information contained in the text is closely related to the compilation of various bibliographic sources using the deductive method, which significantly contributes to the conclusion of the problem raised, achieving effective and efficient results from the development of the same research.